TERTIARY GIANT LACEWINGS (NEUROPTERA: POLYSTOECHOTIDAE): REVISION AND DESCRIPTION OF NEW TAXA FROM WESTERN NORTH AMERICA AND DENMARK - Archibald S.B.; Makarkin V.N. (My University, 2006)
A preliminary definition of the Polystoechotidae (Insecta, Neuroptera) based on wing characters is provided. Tertiary Polystoechotidae are revised; the genus Palaeopsychops Andersen (10 species) and the new collective genus Polystoechotites gen. n. (6 species) are recognised. Ten new species (eight named) are described from the earliest Early Eocene Fur Formation (Denmark) and the Early to early Middle Eocene Okanagan Highlands (Quilchena and Horsefly River, British Columbia, Canada and Republic, Washington, USA): Palaeopsychops quadratus sp. nov. (Fur Formation); Palaeopsychops setosus sp. nov. (Horsefly River); Palaeopsychops marringerae sp. nov., Palaeopsychops timmi sp. nov., Polystoechotites lewisi gen. et sp. nov., Polystoechotites barksdalae gen. et sp. nov., Polystoechotites falcatus gen. et sp. nov. (Republic); Palaeopsychops douglasae sp. nov., Polystoechotites sp. A, Polystoechotites sp. B (Quilchena). Polystoechotes piperatus Cockerell from Late Eocene of Florissant (Colorado, USA) is assigned to Polystoechotites. Neuroptera incertae sedis sp. A (Republic) is determined as either an aberrant polystoechotid, or belonging to a family of psychopsid-like Neuroptera. Palaeopsychops setosus sp. nov. bears a dense cover of macrotrichia across a portion of the wing membrane, not previously known in the order. Extended floating time of polystoechotids increased negative taphonomic bias, in most depositional settings probably lowering their fossil assemblage representation. In some, taphonomic factors such as the presence of mat-forming organisms may have enhanced their fossil representation to greater than their community representation. This scenario is proposed for the Fur Formation, consistent with lithological evidence and palaeogeographic reconstruction. Dispersal of Palaeopsychops between Denmark and the Okanagan Highlands (direction unknown) was probably by the North Atlantic route, not before the late Palaeocene, during periods of continuous land connection between North America and northern Europe. Polystoechotidae in the Eocene, as today, appear to have ranged in forested regions of microthermal to lower mesothermal climate. © The Natural History Museum.
Keywords: FLORISSANT; FOSSIL INSECTS; FUR FORMATION; OKANAGAN HIGHLANDS; TAPHONOMY; ZOOGEOGRAPHY; Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен